More games trainers play: experiential learning exercises - Scannell, Edward E.; Newstrom, John W. (Paris, 1983)
" Get any training session off the ground fast- or jumpstart one whenever it lags- with more than 400 proven activities in the bestselling Games Trainers Play series. Their names may range from 'Tombstone Planning' to 'The Nobel' Prize Winner', but these brilliantly offbeat, unexpected, disarming, fully reproducible games have one serious mission: to coax even the most reluctant groups to talk, laugh, think, and work together. Page after page of fun, easy-to-plan tear-out exercises help you: break the ice and get participants acquainted; shake up outworn habits and perceptions; challenge with thought-provoking brainteasers; test learning and retention; develop communication and listening skills; bring out and involve participant-leaders; win back lethargic, distracted, low-energy groups; encourage creative problem-solving; boost or reinforce a group's self-image; forge cohesive work teams and value object; facilitate transfer of training to the job."